1997
DOI: 10.1038/icb.1997.52
|View full text |Cite
|
Sign up to set email alerts
|

Effects of anti‐endothelial cell antibody in pre‐eclampsia on endothelin‐1 release from cultured endothelial cells

Abstract: Summary In order to investigate the pathophysiologica! significance of anti-endothelial cell antibody (AECA) in pre-eclampsia, the effects of AECA on endothelin-1 (ET-I) and prostaglandin I-, (PGI-,) release from cultured human umbilical vein endothelial cells (HUVEC) was evaluated. Serum samples were taken from 85 pre-eclamptic and 20 normal pregnant women. Anti-endothelial cell antibody was measured by ELISA using HUVEC. The release of ET-1 and 6-keto PGEl-a, a stable metabolite of PGI,, from HUVEC were eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Expression of TFs on AECA-bound endothelial membrane is associated with thrombosis in several clinical settings, such as preeclampsia, systemic sclerosis, and thrombotic thrombocytopenic purpura [80][81][82]. In KD, AECAs might specifically stimulate endothelial cells in vessels that range in size from the vasa vasorum to medium-sized vessels, resulting in local expression of TF.…”
Section: Autoimmunothrombosis In Kdmentioning
confidence: 99%
“…Expression of TFs on AECA-bound endothelial membrane is associated with thrombosis in several clinical settings, such as preeclampsia, systemic sclerosis, and thrombotic thrombocytopenic purpura [80][81][82]. In KD, AECAs might specifically stimulate endothelial cells in vessels that range in size from the vasa vasorum to medium-sized vessels, resulting in local expression of TF.…”
Section: Autoimmunothrombosis In Kdmentioning
confidence: 99%
“…Treatment with ET-1 receptor blockers has been found effective in PAH and digital ulcer prevention in SSc 53. Interestingly, in in vitro studies incubation of HUVECs with AECA-positive sera from patients with SLE and pre-eclampsia resulted in enhanced release of ET-1 54 55. Whether this is also true for sera from AECA-positive patients with SSc, however, needs to be demonstrated.…”
Section: Pathogenic Role Of Aeca In Sscmentioning
confidence: 99%
“…In other words, the relationship between hypertension, cerebral hemorrhage and infarction is complex. Furthermore, studies have suggested immune system involvement in pregnancy hypertension [38][39][40][41], but not in essential hypertension.…”
Section: Pih Susceptibility Genesmentioning
confidence: 99%